Acrylamide in human breast milk - the current state of knowledge - Hanna Mojska (National Institute of Public Health - National Institute of Hygiene, 2022)
Human milk is a first choice in infant nutrition. It not only provides all the nutrients necessary for the proper infant`s development but also contains bioactive factors that provide natural protection against infections. Unfortunately, chemical contaminants can pass to breast milk and pose a health risk for the breastfed infant's health. Acrylamide is a typical process contaminant and in food it is formed as a result of the Maillard reaction. Numerous studies have shown that acrylamide is a neurotoxic and carcinogenic compound. So far there have been published only three studies on the acrylamide content in human milk. In two of them, the acrylamide level in most of the tested samples did not exceed the value of 0.5 μg/L. In the third study, the authors assessed the circulation of acrylamide in the body of two breastfeeding women after consuming products with high acrylamide content. Depending on the time elapsed after the meal, the acrylamide content ranged from 3.17 μg/L to 18.8 μg /L. These studies show that the breastfeeding mothers' diet may have a significant influence on the level of acrylamide in their milk. However, it seems that the acrylamide content in breast milk is also influenced by the time of breast milk collection, including the time elapsed after the mother's meal. To assess the exposure of breastfed infants to acrylamide in human milk, more data is needed on the acrylamide content in human milk at different stages of lactation and using standard protocols for human milk sampling.